2022
DOI: 10.58968/ria.v2i1.137
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis on Sharia Credit Card using Senti-Strength

Abstract: This research was conducted to determine sentiment towards the law and the application of sharia cards issued within a period of 52 years (1970-2022). The technique involves secondary data from the metadata of 98 published publications that are in Dimensions, along with descriptive statistical analysis, meta-analysis, and sentiment analysis, then processed using Microsoft Excel 2019 and SentiStrength software. The results indicate that sharia cards have been the subject of more inquiry in the scientific litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Then this research was continued with sentiment analysis research to find out sentiment from previous research related to zakat regulation and its policies. Sentiment analysis is a type of research that is often used to measure public opinion towards a particular object or issue and became popular in early 2002 (As-salafiyah, Rusydiana, Marlina, et al, 2021;Mu'adzah, 2022). Researchers used SentiStrength software.…”
Section: Methodsmentioning
confidence: 99%
“…Then this research was continued with sentiment analysis research to find out sentiment from previous research related to zakat regulation and its policies. Sentiment analysis is a type of research that is often used to measure public opinion towards a particular object or issue and became popular in early 2002 (As-salafiyah, Rusydiana, Marlina, et al, 2021;Mu'adzah, 2022). Researchers used SentiStrength software.…”
Section: Methodsmentioning
confidence: 99%
“…VOSviewer, developed by Nees Jan van Eck and Ludo Waltman, is a tool used in meta-analysis to visualize the authors and sources of articles related to the theme of Islamic Bank Spin Off. Research using sentiment analysis on Islamic economics can be found at Muadzah (2022), Maulida et al (2022), also Riani et al, (2022).…”
Section: Methodsmentioning
confidence: 99%
“…This method allows the research to categorize the tweets in this study based on the sentiment contained within their text, enabling an analysis of public views and attitudes toward green finance in the context of social media. Other studies using sentiment analysis can be found at Mu'adzah (2022), Maulida et al, (2022), Rusydiana (2022), Rahayu (2022), Maulida & Rusydiana (2023), Zaidan et al, (2022), andNuraini (2022).…”
Section: Methodsmentioning
confidence: 99%